Rhopalurus caribensis, is a synonym of Rhopalurus laticauda (Scorpiones, Buthidae) - FLÓREZ-D., EDUARDO (Revista Colombiana de Entomología, 2012)
Rhopalurus caribensis Teruel & Roncallo, 2008 (n. syn.) is synonymized with R. laticauda Thorell, 1876, based on a review of morphological variations of characters listed by Roncallo and Teruel (2008). The biogeographic assumption presented by Teruel & Roncallo (2008) as an argument to justify the description of R. caribensis is refuted.